Phytoptus atherodes sp. n. (Acari: Eriophyoidea: Phytoptidae) and a supplementary description of Phytoptus hirtae Roivainen 1950 from sedges (Cyperaceae) - Chetverikov, Philipp E. (Zootaxa, 2011)
A new species, Phytoptus atherodes, an eriophyoid mite found on Carex atherodes Spreng. in North-West Russia, is described and a supplementary description of the poorly known species, Phytoptus hirtae Roivainen 1950, from Carex hirta L. is given. P. atherodes sp. n. has deutogyne and protogyne females which differ in the length of the body, prodorsal shield, setae v, φ and с 1; the number of dorsal annuli and length and number of empodial rays. Variability of empodial ray numbers among summer (protogyne) and winter (deutogyne) females of P. atherodes sp. n. and P. hirtae was studied for the first time and may reflect different stages of evolution within the genus Phytoptus.